2022
DOI: 10.1002/aoc.6608
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenyl‐2‐pyridylimine derived d10‐configuration complexes as prospective co‐sensitizers in dye sensitized solar cells

Abstract: Three complexes comprising ferrocenyl‐2‐pyridylimine and three d10 transition metal centers viz. Zn (II), Cd (II), and Hg (II) having formula [M (FcCH=NCH2(2‐py)] (M = Zn (II) (Zn‐Fc), Cd (II) (Cd‐Fc), and Hg (II) (Hg‐Fc); Fc = Ferrocene) are synthesized and their characterization have been done using microanalytical technique, FT‐IR and NMR spectroscopic methods. The optimized molecular geometries for all the three ferrocene‐based complexes revealed that the coordination geometries around the d10‐metal center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…Table 1 presents DSSC performances of previously reported analogous sensitizers comprising. [52][53][54][55] The photovoltaic data suggested that performance of sensitizers investigated in presented study are comparable to the reported analogous sensitizers. However, the cell performance of the sensitizers are relatively inferior to that of the state of the art N719 dye, 52 which partly may be attributed to the relatively poor spectral response and inferior photo-electron transfer.…”
Section: Photovoltaic Performance Of Dsscssupporting
confidence: 81%
See 2 more Smart Citations
“…Table 1 presents DSSC performances of previously reported analogous sensitizers comprising. [52][53][54][55] The photovoltaic data suggested that performance of sensitizers investigated in presented study are comparable to the reported analogous sensitizers. However, the cell performance of the sensitizers are relatively inferior to that of the state of the art N719 dye, 52 which partly may be attributed to the relatively poor spectral response and inferior photo-electron transfer.…”
Section: Photovoltaic Performance Of Dsscssupporting
confidence: 81%
“…[52][53][54][55] The photovoltaic data suggested that performance of sensitizers investigated in presented study are comparable to the reported analogous sensitizers. However, the cell performance of the sensitizers are relatively inferior to that of the state of the art N719 dye, 52 which partly may be attributed to the relatively poor spectral response and inferior photo-electron transfer. However, as compared to the Ru(II)-based N719 sensitizers the sensitizers investigated herein are easy to synthesize and cost effective.…”
Section: Photovoltaic Performance Of Dsscssupporting
confidence: 81%
See 1 more Smart Citation
“…The need for attention about the future global energy production is pointing to the need to harvest the energy of sunlight by improving photovoltaic technology. [1,2] Solar cells transform sunlight into electricity. The photochemical reactions and charge transfer processes are two essential components of energy production using solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these reports, the ferrocene-based complexes have been utilized as co-sensitizers to enhance the DSSC performance of the state-of-the-art N719 dyes. 36 These investigations laid a firm platform to utilise ferrocene-based derivatives as co-sensitizers in DSSCs. The 1,10-phenanthrolene-5,6-dione ligand-based complexes display the potential to exhibit higher stability and have the capability to allow control over redox tenability and also these can engender suitable metalloligands for the generation of functionalized coordination complexes that could be utilized as sensitizers and co-sensitizers in DSSCs.…”
Section: Introductionmentioning
confidence: 99%